High-intensity focused ultrasound for the treatment of hepatic echinococcosis - Chen, Zhenzhen; Salameen, Haitham; Gong, Jianping; Wen, Xuegang (International Surgery Journal, 2021)
Objective of the study was to investigate the safety and effectiveness of high-intensity focused ultrasound (HIFU) to treat hepatic echinococcosis (HE). Eight HE patients treated between 2008 and 2010 were evaluated for the effectiveness of HIFU treatment; the occurrence of complications such as post treatment pain, fever, and skin burns; prognosis; and recurrence. Clinical and imaging evaluation of disease improved after treatment in all eight patients. Postoperatively, all patients experienced changes in liver function that returned to normal within 5 days. Three patients experienced low-grade fever that resolved in 6 days. Six patients complained of right upper quadrant pain that resolved in 7 days. Three patients experienced minor swelling of the skin. No unexpected complications were noted. HIFU was safe and effective for treating HE. It is non-invasive and caused no severe postoperative complications.